Twenty Years of AIRE - Perniola, Roberto (Frontiers in Immunology, 2018)
About two decades ago, cloning of the autoimmune regulator (AIRE) gene materialized one of the most important actors on the scene of self-tolerance. Thymic transcription of genes encoding tissue-specific antigens is activated by AIRE protein and embodies the essence of thymic self-representation. Pathogenic AIRE variants cause the autoimmune polyglandular syndrome type 1, a rare and complex disease that is gaining attention in research on autoimmunity. The animal models of disease, although not identically reproducing the human picture, supply fundamental information on mechanisms and extent of AIRE action: thanks to its multidomain structure, AIRE localizes to chromatin enclosing the target genes, binds to histones and offers an anchorage to multimolecular complexes involved in initiation and post-initiation events of gene transcription. In addition, AIRE enhances mRNA diversity by favoring alternative mRNA splicing. Once synthesized, tissue-specific antigens are presented to, and cause deletion of the self-reactive thymocyte clones. However, AIRE function is not restricted to the activation of gene transcription. AIRE would control presentation and transfer of self-antigens for thymic cellular interplay: such mechanism is aimed at increasing the likelihood of engagement of the thymocytes that carry the corresponding T-cell receptors. Another fundamental role of AIRE in promoting self-tolerance is related to the development of thymocyte anergy, as thymic self-representation shapes at the same time the repertoire of regulatory T cells. Lastly, AIRE seems to replicate its action in the secondary lymphoid organs, albeit the cell lineage detaining such property has not been fully characterized. Delineation of AIRE functions adds interesting data to the knowledge of the mechanisms of self-tolerance and introduces exciting perspectives of therapeutic interventions against the related diseases.